Assessing Penalties of Foreigners who Commit an International Trafficking Drugs in Indonesia: a Case of Mary Jane - Itsna Qurrotul 'Ain (FH 16 UMY 22, 2016)
Nowadays, Indonesia has become the target of international trafficking drugs. Issuing jurisdiction and a matter of law enforcement in Indonesia are two main problems dealing to illicit trafficking drugs committed by foreigners. Mary Jane who smuggling 2.6 kilograms of heroin in Indonesia, has no death execution yet because of the Philipine’s court proceeding assumption related on Jane’s status of victim of trafficking in person. Mary Jane’s case is a reminder of government to ensure the implementation of Indonesian law which connected also to the International Convention for the human trafficking criminal acts or Palermo Protocol. The type of this research is a normative legal research with statute approach and analytical approach. By using a qualitative descriptive method, this study would analyze how are International law and National law regulates on penalties of foreigner who commit an international trafficking drugs in Indonesia: a case of Mary Jane. Finally, the result shows Indonesia’s jurisdiction is claimed by seeing related principle of law, United Nation Convention against Illicit Traffick on Narcotic Drugs and Psychotropic Substances 1988, and Indonesian Penal Code. In the case of Mary Jane, by reflecting the sovereignty of nation principle, Indonesia absolutely has the right in implementing its law. On the sake of justice and legal certainty, Indonesia’s court proceeding should re-examine Mary Jane’s case carefully under the novum. Furthermore, the policy upon Mary Jane’s case left to Indonesian law to be decided with no influenced by other state domestic affairs.